Nitrogen-doped carbon aerogel as well as preparation method and application thereof
Through frozen crystallization polymerization technology and activator treatment, a three-dimensional interconnected carbon aerogel with high nitrogen content was prepared, which solved the problems of complex processes and single material structure of the existing methods, and achieved efficient CO2 adsorption and industrial production of materials.
Patent Information
- Application Number
- CN202510086549.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-20
Smart Images

Figure CN119735197A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of carbon aerogel materials, and in particular relates to a nitrogen-doped carbon aerogel and a preparation method and application thereof. Background Art
[0002] Carbon dioxide capture and storage (CCS) is an important technical path to reduce carbon emissions and address global warming. Among them, adsorption technology has attracted much attention due to its high efficiency, especially when the adsorbent has a three-dimensional interconnected pore structure and can achieve rapid gas transmission, its application potential is more significant. Carbon aerogels show broad application prospects due to their high specific surface area, adjustable density, high porosity, flexible pore size distribution and excellent electrical conductivity. Compared with traditional carbon aerogels, nitrogen-doped carbon aerogels have better performance due to more active sites. After nitrogen atoms replace carbon atoms in carbon materials, the morphology, structure and chemical properties of the materials can be effectively regulated to improve their reactivity. In addition, the introduction of nitrogen atoms can significantly enhance the alkaline active sites on the surface of carbon materials, thereby improving their adsorption capacity and selectivity for acidic CO2 molecules. By directly activating nitrogen-containing polymers, not only can complex post-processing steps be avoided, but also precise control of chemical composition can be achieved, further improving adsorption performance. At the same time, this method can effectively alleviate the blockage of active sites and diffusion channels that may be caused by post-processing, thereby maintaining the efficient adsorption performance of the material.
[0003] The Chinese patent application number 201510649028.2 (a nitrogen-doped carbon aerogel and its preparation method) discloses a method for preparing nitrogen-doped carbon aerogel, wherein the process is to add resorcinol and formaldehyde solution to a phloroglucinol solution, stir and then add potassium carbonate to form an aerogel, the aerogel is treated with acetone solvent exchange to prepare a phloroglucinol-resorcinol-formaldehyde gel, and a dry gel is obtained by supercritical carbon dioxide extraction and drying steps, and finally the nitrogen-doped carbon aerogel is prepared by carbonization. The Chinese patent application number 201711206128.3 (a method for preparing nitrogen-doped carbon aerogel) proposes a preparation process using bean dregs as a carbon source, which specifically comprises mixing bean dregs with concentrated sulfuric acid to form a carbon sol precursor, diluting and subjecting the mixture to microwave hydrothermal treatment to obtain a brown precipitate; the precipitate is filtered, dried and carbonized at high temperature to prepare the nitrogen-doped carbon aerogel; however, these preparation methods have complex process flows and require the use of professional equipment such as a supercritical carbon dioxide extractor, which is time-consuming. The raw materials are expensive, including highly toxic chemicals such as resorcinol and formaldehyde. In addition, the structure of the prepared carbon aerogel is relatively simple and difficult to meet the needs of practical applications. Therefore, it is urgent to develop new adsorbents with higher selectivity and adsorption efficiency to promote the efficient development of CO2 capture technology. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a nitrogen-doped carbon aerogel and a preparation method and application thereof.
[0005] The carbon aerogel adopts the strategy of frozen crystallization and subsequent polymerization, and uses two low-cost and nitrogen-rich precursors, acrylamide (AM) and aniline (ANI), to prepare a three-dimensional interconnected carbon aerogel. First, a highly absorbent three-dimensionally interconnected polyacrylamide (PAM) medium is prepared; then, using its high-strength absorbency, the reaction solution of aniline is fully absorbed at low temperature (ensuring sufficient aniline reaction solution). Under freezing conditions, aniline is evenly dispersed and orderly polymerized under the action of ice crystals, solving the problem of difficult dispersion of agglomerates prepared by traditional polyaniline (PANI). Finally, an activator is used to activate the aerogel to form pores. The carbon aerogel significantly improves the adsorption capacity of CO2 due to its high nitrogen content, rich in a large number of alkaline active sites, and three-dimensionally interconnected microporous structure.
[0006] To achieve the above object, the technical solution of the present invention is as follows: A method for preparing nitrogen-doped carbon aerogel comprises the following steps: (1) Preparation of highly absorbent PAM aerogel Dissolve acrylamide (AM) and N,N'-methylenebisacrylamide (MBA) crosslinkers in deionized water, fill with nitrogen to drive out oxygen, and stir until completely dissolved to form a uniform solution; add pre-cooled ammonium persulfate (APS) and N,N,N',N'-tetramethylethylenediamine (TEMED) to the solution at -5 ~ 0°C; after stirring evenly, quickly pour into a silica gel mold, freeze polymerize at -40 ~-25°C; then melt, wash, and dry to obtain a PAM aerogel with a three-dimensional continuous pore structure with high absorbency; The present invention is to obtain a PAM aerogel with a highly absorbent three-dimensional pore structure, and adopts a freezing crystallization polymerization method, which realizes copolymerization of an acrylamide monomer and an aqueous solution of an N,N'-methylenebisacrylamide (MBA) crosslinking agent using water as a solvent; (2) PANI is evenly dispersed and polymerized Aniline (ANI) was added dropwise into an acidic solution under a nitrogen atmosphere, stirred thoroughly to ensure complete dissolution, and then pre-cooled; ammonium persulfate (APS) was dissolved in deionized water using microwave-assisted ultrasound and pre-cooled; when small ice crystals appeared in the two pre-cooled solutions, the two pre-cooled solutions were quickly mixed and stirred thoroughly; the pre-cooled PAM aerogel was then added, mixed evenly, and the mixture was placed in an environment of -40 ~ -25℃ for freezing polymerization, and then melted and dried; during the cooling and crystallization of the mixed solution, the solvent water crystallized into a porogen and separated from the solute phase, and the solute phase continued to concentrate, prompting the ANI solute to self-assemble in the three-dimensionally interconnected PAM aerogel to complete polymerization and spreading, and finally forming a polymer (PANI@PAM) aerogel; (3) Activation and carbonization treatment The PANI@PAM aerogel is fully crushed and ground under nitrogen, and an activator is added and mixed evenly; it is fully calcined and activated at a certain heating rate in a flowing nitrogen (N2) atmosphere; it is then soaked in an acidic solution to remove the residual activator, and washed and dried completely to obtain the nitrogen-doped carbon aerogel. The activation of the polymer can avoid the loss of active sites and retain the three-dimensional interconnected pore structure of the PAM aerogel, providing a fast channel for the high-speed flow of CO2.
[0007] Preferably, in the reaction system in step (1), the mass volume ratio of acrylamide (AM), N,N'-methylenebisacrylamide (MBA), and deionized water is (0.5 g ~ 1.3 g): (0.1 g ~ 0.2 g): (5 mL ~ 20 mL).
[0008] Further preferably, the ammonium persulfate (APS) in step (1) is added in the form of 0.3 mL to 0.6 mL of an APS aqueous solution having a mass fraction of 5% to 20%, and the N,N,N',N'-tetramethylethylenediamine (TEMED) is added in the form of 0.1 mL to 0.3 mL of a TEMED aqueous solution having a mass fraction of 5% to 15%.
[0009] Preferably, the nitrogen filling and oxygen displacing time in step (1) is 2 to 4 hours; the polymerization is performed at -40 to -20°C for 16 to 24 hours; the melting temperature is 20 to 26°C; and the washing is performed by ultrasonic cleaning with ethanol and washing with deionized water until the washing is neutral to completely remove unreacted monomers.
[0010] Preferably, the acidic solution in step (2) is hydrochloric acid (HCl) or phytic acid (C6H 18 O 24 P6), an aqueous solution of sulfuric acid (H2SO4) or nitric acid (HNO3), more preferably, the acidic solution is hydrochloric acid.
[0011] Preferably, the concentration of the acidic solution in step (2) is 1 to 3 mol / L, and the volume is 4 to 6 mL; the pre-cooling temperature is -10 to 0°C.
[0012] Preferably, the volume of aniline in step (2) is 2 to 5 mL, and the concentration is greater than 99.5%; the mass of ammonium persulfate is 1 to 2 g, and the volume is 1 to 2 mL; the mass of PAM aerogel is 0.1 to 0.5 g; the freezing polymerization time at -40 to -25°C is 18 to 24 h; the melting temperature is 30 to 40°C; and the drying is performed in an oven at 40 to 50°C for 12 to 18 h.
[0013] Preferably, the activator in step (3) is potassium carbonate (K2CO3), potassium hydroxide (KOH), phosphoric acid (H3PO4), and more preferably, the activator is K2CO3 or KOH.
[0014] Preferably, the mass ratio of the activator to the PANI@PAM aerogel in step (3) is (1-4):1.
[0015] Preferably, the flow rate of the flowing nitrogen in step (3) is 0.4 to 1 L / min; the calcination heating rate is 1 to 10°C / min, the calcination temperature is 400 to 900°C, and the sufficient calcination activation time is 2 to 4 h.
[0016] Preferably, the acidic solution in step (3) is hydrochloric acid (HCl), or an aqueous solution of nitric acid (HNO3), sulfuric acid (H2SO4), formic acid (HCOOH), acetic acid (CH3COOH) or oxalic acid (C2H2O4), and more preferably, the acidic solution is hydrochloric acid.
[0017] Preferably, the concentration of the acidic solution in step (3) is 1 to 3 mol / L, and the soaking time is 4 to 6 h.
[0018] Preferably, the washing in step (3) is performed by ultrasonic cleaning with ethanol and cleaning with deionized water until neutral; and the drying is performed in an oven at 90° C. to 150° C. for 10 h to 12 h.
[0019] Nitrogen-doped carbon aerogel prepared by the above method.
[0020] Application of the nitrogen-doped aerogel in CO2 adsorption.
[0021] Beneficial Effects The present invention constructs a hierarchical carbon aerogel adsorbent with a spatially three-dimensional continuous nitrogen-rich structure (~10%) and a pore wall with abundant micropores (0.4 ~ 0.9 nm) through frozen crystallization polymerization and activation technology. From a molecular level analysis, the essence of the adsorbent matrix of the present invention is a three-dimensional network of polymer chains with a highly absorbent and highly interconnected pore structure, which provides a good place for the reaction of the aniline mixed solution. When the aniline solution enters the three-dimensional network, the aqueous solution crystallizes due to rapid cooling to form a pore-forming agent. The solute aniline is highly enriched and covers the surface of the three-dimensional network under the action of ice crystals. Under the action of the initiator, polymerization extension is carried out to complete self-assembly. This frozen crystallization polymerization method can break the strong hydrogen bonding effect formed by aniline during polymerization, thereby increasing its coverage in the material and the nitrogen content of the polymer. Under the action of the activator, a large number of microporous structures are generated on the surface of the polymer, which greatly increases the specific surface area of the material. The specific surface area of the prepared carbon aerogel material is 200 ~ 1500 m 2 / g, CO2 adsorption capacity is 0.55~4.5 mmol / g. And it has good stability, and can still maintain more than 95% of the initial adsorption capacity after 10 cycles of adsorption-desorption.
[0022] The present invention uses low-priced, high-nitrogen-content aniline and acrylamide as carbon sources, adopts a preparation strategy combining frozen crystallization polymerization with high-temperature carbonization, has a simple process, and is suitable for large-scale industrial production. The obtained product has the characteristics of rich nitrogen content, reasonable pore classification, high specific surface area, stable structure, etc., and can be widely used in the field of efficient CO2 adsorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] FIG1 is a flow chart of the preparation of nitrogen-doped carbon aerogel of the present invention. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with specific embodiments. The advantages and features of the present invention will be more clearly reflected in the description. However, the embodiments are only exemplary and do not constitute any limitation to the scope of the present invention. Those skilled in the art will appreciate that, without departing from the spirit and scope of the present invention, the details and forms of the technical solution may be modified or replaced, and these modifications and replacements all belong to the protection scope of the present invention.
[0025] Example 1 A method for preparing nitrogen-doped carbon aerogel comprises the following steps: (1) 0.9 g acrylamide (AM) monomer and 0.18 g N,N'-methylenebisacrylamide (MBA) crosslinker were added to 10 mL of deionized water, nitrogen was introduced to drive out oxygen for 3 h, and the mixture was stirred until it was completely dissolved to form a uniform solution. When the temperature dropped to -5 °C, 0.4 mL of pre-cooled 10% ammonium persulfate (APS) aqueous solution and 0.2 mL of 10% N,N,N',N'-tetramethylethylenediamine (TEMED) aqueous solution were added to the solution. After stirring evenly, the mixture was quickly poured into a silica gel mold (size: length × width × height = 60 mm × 30 mm × 40 mm) and placed in a -20 °C freezer for freezing polymerization for 24 h. After the end, the ice crystals were melted at room temperature, rinsed with deionized water and dried under ambient atmospheric pressure to obtain PAM aerogel.
[0026] (2) Prepare 4.75 mL of 3 mol / L HCl solution, slowly add it dropwise to 2 mL of aniline (ANI), stir thoroughly to ensure complete dissolution and cool to -10°C. Add 1.3 g of APS to another beaker, dissolve it in 2 mL of deionized water using an ultrasonic vibrator and precool the solution. When small ice crystals appear in the precooled solution, quickly mix the two cooled solutions and stir thoroughly. Subsequently, add 0.2 g of precooled PAM aerogel, mix well, and place the mixture in a -30°C freezer to react for 24 h. After the reaction is complete, melt it in deionized water at 35°C, and place the resulting product in a 50°C oven to dry for 12 to 18 h to obtain PANI@PAM 3D porous structure aerogel.
[0027] (3) The obtained aerogel material was ground into powder and uniformly mixed with an activator (K2CO3) in a mortar at a mass ratio of 1:2. Then, the mixture was placed in a tube furnace and calcined and activated in a 0.5 L / min flowing nitrogen (N2) atmosphere with a heating rate of 5°C / min and a calcination temperature of 650°C for 2 h. After activation, it was immersed in a 1 mol / L HCl solution for 5 h to remove the residual activator. Subsequently, it was repeatedly washed with deionized water and ethanol solution until neutral, and finally dried at 95°C for 12 h.
[0028] The specific surface area of the carbon aerogel adsorbent prepared in Example 1 is 1354.63 m 2 / g, micropore volume 0.60cm 3 / g, the micropores are distributed in 0.55 ~ 0.76 nm, and have good CO2 affinity. The carbon aerogel adsorbent prepared by the reaction system formula in Example 1 has a CO2 saturation adsorption capacity of 4.32 mmol / g at 25°C and 101 kPa, which is 89.76% higher than the adsorption capacity without adding an activator. After 10 adsorption-desorption cycles, the adsorption capacity of the adsorbent is still as high as 95% of the initial adsorption capacity.
[0029] Example 2 A method for preparing nitrogen-doped carbon aerogel comprises the following steps: (1) 1.0 g acrylamide (AM) monomer and 0.18 g N,N'-methylenebisacrylamide (MBA) crosslinker were added to 20 mL of deionized water, nitrogen was filled to drive out oxygen for 3 h, and stirred until completely dissolved to form a uniform solution. When the temperature dropped to -5 °C, 0.3 mL of pre-cooled 10% ammonium persulfate (APS) and 0.3 mL of 10% N,N,N',N'-tetramethylethylenediamine (TEMED) were added to the solution. After stirring evenly, it was quickly poured into a silica gel mold (size: length × width × height = 60 mm × 30 mm × 40 mm) and placed in a -20 °C freezer for freezing polymerization for 24 h. After the end, the ice crystals were melted at room temperature, rinsed with deionized water and dried under ambient atmospheric pressure to obtain PAM aerogel.
[0030] (2) Prepare 4.75 mL of 1.5 mol / L phytic acid solution, slowly add it to 2 mL of aniline (ANI), stir thoroughly to ensure complete dissolution and cool to -10°C. Add 1.5 g of APS to another beaker, dissolve it in 2 mL of deionized water using an ultrasonic vibrator and precool the solution. When small ice crystals appear in the precooled solution, quickly mix the two cooled solutions and stir thoroughly. Subsequently, add 0.2 g of precooled PAM aerogel, mix well, and place the mixture in a -30°C freezer to react for 24 h. After the reaction is complete, melt it in deionized water at 35°C, and place the resulting product in a 50°C oven to dry for 12 to 18 h to obtain PANI@PAM 3D porous structure aerogel.
[0031] (3) The obtained aerogel material was ground into powder and uniformly mixed with an activator (KOH) in a mortar at a mass ratio of 1:2. Then, the mixture was placed in a tube furnace and calcined and activated in a 0.5 L / min flowing nitrogen (N2) atmosphere with a heating rate of 10°C / min and a calcination temperature of 750°C for 2 h. After activation, it was immersed in a 1 mol / L HCl solution for 5 h to remove the residual activator. Subsequently, it was repeatedly washed with deionized water and ethanol solution until neutral, and finally dried at 95°C for 12 h.
[0032] The specific surface area of the carbon aerogel adsorbent prepared in Example 2 is 1175.67 m 2 / g, micropore volume 0.36cm 3 / g, the micropores are distributed in the range of 0.45 ~ 0.70 nm, and have good CO2 affinity. The carbon aerogel adsorbent prepared by the reaction system formula in Example 2 has a CO2 saturation adsorption capacity of 3.81 mmol / g under the conditions of 25°C and 101 kPa, which is 85.56% higher than the adsorption capacity without adding the activator.
[0033] Example 3 A method for preparing nitrogen-doped carbon aerogel comprises the following steps: (1) 0.5 g acrylamide (AM) monomer and 0.2 g N,N'-methylenebisacrylamide (MBA) crosslinker were added to 10 mL of deionized water, nitrogen was filled to drive out oxygen for 3 h, and stirred until completely dissolved to form a uniform solution. When the temperature dropped to -5 °C, 0.5 mL of pre-cooled 15% ammonium persulfate (APS) and 0.3 mL of 15% N,N,N',N'-tetramethylethylenediamine (TEMED) were added to the solution. After stirring evenly, it was quickly poured into a silica gel mold (size: length × width × height = 60 mm × 30 mm × 40 mm) and placed in a -20 °C freezer for freezing polymerization for 24 h. After the end, the ice crystals were melted at room temperature, rinsed with deionized water and dried under ambient atmospheric pressure to obtain PAM aerogel.
[0034] (2) Prepare 5 mL of 1.5 mol / L HCl solution, slowly add it to 2 mL of aniline (ANI), stir thoroughly to ensure complete dissolution and cool to -10°C. Add 2.0 g of APS to another beaker, dissolve it in 2 mL of deionized water using an ultrasonic vibrator and precool the solution. When small ice crystals appear in the precooled solution, quickly mix the two cooled solutions and stir thoroughly. Subsequently, add 0.2 g of precooled PAM aerogel, mix well, and place the mixture in a -30°C freezer to react for 24 h. After the reaction is complete, melt it in deionized water at 35°C, and place the resulting product in a 50°C oven to dry for 12 to 18 h to obtain PANI@PAM 3D porous structure aerogel.
[0035] (3) The obtained aerogel material was ground into powder and uniformly mixed with an activator (KOH) in a mortar at a mass ratio of 1:4. Then, the mixture was placed in a tube furnace and calcined and activated in a 1 L / min flowing nitrogen (N2) atmosphere with a heating rate of 4 °C / min and a calcination temperature of 850 °C for 1 h. After activation, it was immersed in a 1 mol / L HCl solution for 5 h to remove the residual activator. Subsequently, it was repeatedly washed with deionized water and ethanol solution until neutral, and finally dried at 95 °C for 12 h.
[0036] The specific surface area of the carbon aerogel adsorbent prepared in Example 3 is 324.34 m 2 / g, micropore volume 0.22cm 3 / g, the micropores are distributed in the range of 0.72 ~ 0.93 nm, and have good CO2 affinity. The carbon aerogel adsorbent prepared by the reaction system formula in Example 3 has a CO2 saturation adsorption capacity of 0.97 mmol / g under the conditions of 25°C and 101 kPa, which is 43.30% higher than the adsorption capacity without adding the activator.
[0037] Comparative Example 1 A method for preparing nitrogen-doped carbon aerogel comprises the following steps: (1) 0.9 g acrylamide (AM) monomer and 0.18 g N,N'-methylenebisacrylamide (MBA) crosslinker were added to 10 mL of deionized water, nitrogen was introduced to drive out oxygen for 3 h, and the mixture was stirred until it was completely dissolved to form a uniform solution. When the temperature dropped to -5 °C, 0.4 mL of pre-cooled 10% ammonium persulfate (APS) and 0.2 mL of 10% N,N,N',N'-tetramethylethylenediamine (TEMED) were added to the solution. After stirring evenly, the mixture was quickly poured into a silica gel mold (size: length × width × height = 60 mm × 30 mm × 40 mm) and placed in a -20 °C freezer for freezing polymerization for 24 h. After the polymerization, the ice crystals were melted at room temperature, rinsed with deionized water and dried under ambient atmospheric pressure to obtain PAM aerogel.
[0038] (2) Prepare 4.75 mL of 3 mol / L HCl solution, slowly add it to 2 mL of aniline (ANI), stir thoroughly to ensure complete dissolution and cool to -10°C. Add 1.3 g of APS to another beaker, dissolve it in 2 mL of deionized water using an ultrasonic vibrator and precool the solution. When small ice crystals appear in the precooled solution, quickly mix the two cooled solutions and stir thoroughly. Subsequently, add 0.2 g of precooled PAM aerogel, mix well, and place the mixture in a -30°C freezer to react for 24 h. After the reaction is complete, melt it in deionized water at 35°C and dry the resulting product in an oven at 50°C to obtain PANI@PAM 3D porous structure aerogel.
[0039] (3) The obtained aerogel material was ground into powder, placed in a tubular furnace, and calcined in a 0.5 L / min flowing nitrogen (N2) atmosphere, with a heating rate of 5°C / min and a calcination temperature of 650°C for 2 h. After calcination, it was immersed in a 1 mol / L HCl solution for 5 h. Subsequently, it was repeatedly washed with deionized water and ethanol solution until neutral, and finally dried at 95°C for 12 h.
[0040] The specific surface area of the carbon aerogel adsorbent prepared in Comparative Example 1 is 1.56 m 2 / g, micropore volume 0.03 cm 3 / g, and the saturated adsorption capacity of CO2 is 0.55 mmol / g at 25℃ and 101 kPa.
Claims
1. A method for preparing nitrogen-doped carbon aerogel, characterized in that: The following steps are involved: (1) Preparation of highly absorbent PAM aerogel Dissolving acrylamide and N,N'-methylenebisacrylamide crosslinking agent in deionized water, filling with nitrogen to drive out oxygen, and stirring until completely dissolved to form a uniform solution; adding pre-cooled ammonium persulfate and N,N,N',N'-tetramethylethylenediamine to the solution at -5 ~ 0°C; after stirring evenly, quickly pouring into a silica gel mold, and freeze-polymerizing at -40 ~ -25°C; then melting, washing, and drying to obtain a PAM aerogel with a three-dimensional continuous pore structure with high absorbency; (2) PANI is evenly dispersed and polymerized Aniline was added dropwise to the acidic solution under nitrogen atmosphere, stirred well to ensure complete dissolution, and then pre-cooled; Ammonium persulfate was dissolved in deionized water using microwave-assisted ultrasound and pre-cooled; when small ice crystals appeared in the two pre-cooled solutions, the two pre-cooled solutions were quickly mixed and stirred thoroughly; then the pre-cooled PAM aerogel was added, mixed evenly, and the mixture was placed in an environment of -40 ~ -25℃ for freeze polymerization, and then melted and dried; finally, the polymer PANI@PAM aerogel was formed; (3) Activation and carbonization treatment The PANI@PAM aerogel is fully crushed and ground under nitrogen, and an activator is added and mixed evenly; it is fully calcined and activated at a certain heating rate under a flowing nitrogen atmosphere; it is then soaked in an acidic solution to remove the residual activator, and washed and dried completely to obtain the nitrogen-doped carbon aerogel.
2. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: In the reaction system of step (1), the mass volume ratio of acrylamide, N,N'-methylenebisacrylamide and deionized water is (0.5 g ~ 1.3 g): (0.1 g ~ 0.2 g): (5 mL ~ 20 mL); Preferably, the ammonium persulfate in step (1) is added in the form of 0.3 mL to 0.6 mL of an APS aqueous solution having a mass fraction of 5% to 20%, and the N,N,N',N'-tetramethylethylenediamine is added in the form of 0.1 mL to 0.3 mL of a TEMED aqueous solution having a mass fraction of 5% to 15%.
3. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: The nitrogen filling and oxygen displacing time in step (1) is 2 to 4 hours; the polymerization is carried out at -40 to -20°C for 16 to 24 hours; the melting temperature is 20 to 26°C; and the washing is carried out by ultrasonic cleaning with ethanol and washing with deionized water until neutral to completely remove unreacted monomers.
4. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: The acidic solution in step (2) is hydrochloric acid, or an aqueous solution of phytic acid, sulfuric acid or nitric acid; preferably, the acidic solution is hydrochloric acid; preferably, the concentration of the acidic solution in step (2) is 1 to 3 mol / L, and the volume is 4 to 6 mL; the pre-cooling temperature is -10 to 0°C.
5. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: The volume of aniline in step (2) is 2 to 5 mL, and the concentration is greater than 99.5%; the mass of ammonium persulfate is 1 to 2 g, and the volume is 1 to 2 mL; the mass of PAM aerogel is 0.1 to 0.5 g; the freezing polymerization time at -40 to -25°C is 18 to 24 h; the melting temperature is 30 to 40°C; and the drying is performed in an oven at 40 to 50°C for 12 to 18 h.
6. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: In step (3), the activator is potassium carbonate, potassium hydroxide or phosphoric acid; preferably, the activator is K2CO3 or KOH; Preferably, the mass ratio of the activator to the PANI@PAM aerogel in step (3) is (1-4):
1.
7. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: The flow rate of the flowing nitrogen in step (3) is 0.4 to 1 L / min; the calcination heating rate is 1 to 10°C / min, the calcination temperature is 400 to 900°C, and the sufficient calcination activation time is 2 to 4 h; Preferably, the acidic solution in step (3) is hydrochloric acid, or an aqueous solution of nitric acid, sulfuric acid, formic acid, acetic acid or oxalic acid. More preferably, the acidic solution is hydrochloric acid.
8. The method for preparing nitrogen-doped carbon aerogel according to claim 1, characterized in that: In step (3), the concentration of the acidic solution is 1 to 3 mol / L, and the soaking time is 4 to 6 h; Preferably, the washing in step (3) is performed by ultrasonic cleaning with ethanol and cleaning with deionized water until neutral; and the drying is performed in an oven at 90° C. to 150° C. for 10 h to 12 h.
9. Nitrogen-doped carbon aerogel prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the nitrogen-doped carbon aerogel according to claim 9 in CO2 adsorption.
Citation Information
Patent Citations
Nitrogen-doped carbon aerogel and preparation method thereof
CN105152159A
Preparation method of in-situ self-assembling N-doped super-hydrophilic carbon aerogel supercapacitor electrode material
CN105480962A
Preparation method of polyaniline aerogel / bamboo-based activated carbon composite material
CN111199836A
Amidoxime-based frozen gel as well as preparation method and application thereof
CN117920154A
Carbon aerogel material with multi-element pore diameter distribution and pore wall structure and preparation method of carbon aerogel material
CN118723990A